2007
DOI: 10.1107/s1600536806053840
|View full text |Cite
|
Sign up to set email alerts
|

N-[(2-Hydroxynaphthalen-1-yl)(phenyl)methyl]acetamide

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean (C-C) = 0.002 Å R factor = 0.045 wR factor = 0.113 Data-to-parameter ratio = 13.2 For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…1. In the structure, all bond lengths and angles are within normal ranges (Allen et al, 1987), and comparable with those in previously reported structure (Mosslemin et al, 2007). The bond distance of C18=O4 is 1.222 (2) Å, which is typical for double bonds (Liu & Li., 2004).…”
Section: S1 Commentsupporting
confidence: 88%
See 1 more Smart Citation
“…1. In the structure, all bond lengths and angles are within normal ranges (Allen et al, 1987), and comparable with those in previously reported structure (Mosslemin et al, 2007). The bond distance of C18=O4 is 1.222 (2) Å, which is typical for double bonds (Liu & Li., 2004).…”
Section: S1 Commentsupporting
confidence: 88%
“…For the properties and potential applications of amide-type compounds and their metal ion complexes, see: Saravanakumar et al (2005); Yin et al (2004). For related structures, see: Mosslemin et al (2007); Zia-ur-Rehman et al (2008). For bond-length data, see: Allen et al (1987); Liu & Li (2004).…”
Section: Related Literaturementioning
confidence: 99%
“…1. In the structure, all bond lengths are comparable with those in previously reported structures (Mosslemin et al, 2007, NizamMohideen et al, 2009. Atom…”
Section: Related Literaturesupporting
confidence: 87%
“…For further synthetic details, see: Shaterian et al (2008). For related structures, see: Mosslemin et al (2007); NizamMohideen et al (2009 Data collection: APEX2 (Bruker, 2004); cell refinement: SAINT (Bruker, 2004); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: SHELXTL (Sheldrick, 2008); software used to prepare material for publication: SHELXTL.…”
Section: Related Literaturementioning
confidence: 99%
“…These contacts account for 13.0% and are characterized by two symmetrical peaks with d i + d e = 1.8 Å ; this reveals the presence of strong OÁ Á ÁH contacts that are characteristic of C-HÁ Á ÁO and O-HÁ Á ÁO hydrogen bonds. (Mosslemin et al, 2007), N-[(2hydroxynaphthalen-1-yl)(4-methylphenyl)methyl]acetamide (Khanapure et al, 2015) and N-[(2-hydroxy-1-naphthyl)(3nitrophenyl)methyl]acetamide (NizamMohideen et al, 2009). Three of these compounds involve N-[(2-hydroxynaphthalen-1-yl) (Bazgir et al, 2006;Mosslemin et al, 2007;Khanapure et al, 2015); in these analogues, the naphthalene ring system is inclined to the benzene ring by 81.54, 82.10 and 82.50 respectively, but in the hydroxy-1-naphthyl compound (NizamMohideen et al, 2009), the dihedral angle is 81.9 , compared with 78.32 (6) and 84.70 (6) in molecules A and B of the title compound.…”
Section: Figurementioning
confidence: 99%